2021
DOI: 10.1101/2021.04.27.441707
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Therapeutic effect of CT-P59 against SARS-CoV-2 South African variant

Abstract: The global circulation of newly emerging variants of SARS-CoV-2 is a new threat to public health due to their increased transmissibility and immune evasion. Moreover, currently available vaccines and therapeutic antibodies were shown to be less effective against new variants, in particular, the South African (SA) variant, termed 501Y.V2 or B.1.351. To assess the efficacy of the CT-P59 monoclonal antibody against the SA variant, we sought to perform as in vitro binding and neutralization assays, and in vivo ani… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In adult studies, allergic reactions, anaphylaxis, or infusion-related reactions were the main reported serious side effects occurring in bamlanivimab (2.3% of patients experienced local reactions), 14 casirivimab/imdevimab (1.4% grade ≥2 infusionrelated reaction), 15 sotrovimab (1% infusion-related reactions and 1 patient, ie, <1%, with infusion-related dyspnea) 16,17 and regdanvimab (2.9% with hypertriglyceridemia, 1% infusion-related reaction, 2 patients, ie, 8.3%, in the phase 1 study with hepatocellular injury). [18][19][20] Although studies with head-to-head comparisons are lacking, mAbs are thought to cause fewer side effects such as serum sickness, allergic reactions or life-threatening anaphylaxis than traditional serum therapy or polyclonal preparations (eg, convalescent plasma). 21 Due to data scarcity in children, despite promising studies in adults, a United States expert consortium in 2021 did not recommend the routine use of imdevimab and bamlanivimab in children, even in cases of high risk for disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…In adult studies, allergic reactions, anaphylaxis, or infusion-related reactions were the main reported serious side effects occurring in bamlanivimab (2.3% of patients experienced local reactions), 14 casirivimab/imdevimab (1.4% grade ≥2 infusionrelated reaction), 15 sotrovimab (1% infusion-related reactions and 1 patient, ie, <1%, with infusion-related dyspnea) 16,17 and regdanvimab (2.9% with hypertriglyceridemia, 1% infusion-related reaction, 2 patients, ie, 8.3%, in the phase 1 study with hepatocellular injury). [18][19][20] Although studies with head-to-head comparisons are lacking, mAbs are thought to cause fewer side effects such as serum sickness, allergic reactions or life-threatening anaphylaxis than traditional serum therapy or polyclonal preparations (eg, convalescent plasma). 21 Due to data scarcity in children, despite promising studies in adults, a United States expert consortium in 2021 did not recommend the routine use of imdevimab and bamlanivimab in children, even in cases of high risk for disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…This neutralizing antibody shows some efficacy in vitro in decreasing viral loads of various SARS-CoV-2 isolates, e.g. South-African and a Korean, as well as the wild type of the virus [68,69]. CT-P53 showed significantly inhibited viral replication in vivo [69] and a clinical study involving approximately 200 patients indicated that this agent increases viral clearance and decreases time to negative conversion as well as hospitalization [70].…”
Section: Neutralizing Antibodiesmentioning
confidence: 99%
“…Tixagevimab did not show activity against omicron either, while cilgavimab retained some activity (albeit 15-fold lower), resulting in a 42-fold reduction of the activity of the tixagevimab/cilgavimabb cocktail against omicron. On the other hand, sotrovimab and bebtelovimab are still retaining activity against beta, delta, and omicron (Cameroni et al, 2021;Corti et al, 2021;Ryu and Kang, et al, 2021;Ryu and Song, et al, 2021;Hoffmann et al, 2021;Planas et al, 2021;Westendorf et al, 2022;Ju et al, 2022;Li et al, 2022;Touret et al, 2022). This demonstrates that several of the commercially available therapeutic mAbs lose their activity against multiple SARS-CoV-2 variants of concern (VoC).…”
Section: Introductionmentioning
confidence: 99%